Histopathological aspects of the relationship Saimiri sciureus × Prosthenorchis elegans (Acanthocephala) in a preserved environment of an urban rainforest fragment - Rogério Antonio Ribeiro Rodrigues; Washington Luiz Assunção Pereira; Raul Henrique da Silva Pinheiro; Elane Guerreiro Giese (Revista Brasileira de Parasitologia Veterinária)
Abstract Non-human primates are potential hosts for helminths of various phyla, and the presence of these parasites can cause changes in organ morphology and functionality. In this study, we present the alterations induced by the presence of acanthocephalan parasites in the small intestine of a snub-nosed monkey that died in the Bosque Rodrigues Alves, municipality of Belém, Pará state, Brazil. Ten specimens of Saimiri sciureus had their intestines analyzed and the parasites recovered were cleaned, quantified, fixed and observed using light microscopy and scanning electron microscopy, and fragments of the intestine were separated for histological analysis to identify the alterations. All the animals were parasitized, and a total of 50 specimens representing the Acanthocephala Phylum were recovered, which morphologically showed characteristics compatible with Prosthenorchis elegans (Diesing, 1851). Light microscopy revealed the presence of parasites attached to the mucosal layer, passing through the underlying layers until they reached the muscular layer. Scanning electron microscopy showed the tissue lesions caused by the proboscis hooks and the flattening of the intestinal villi in the presence of the parasite. The presence of the parasites in the intestine changed the morphology of the organ, possibly causing loss of functionality at the site of attachment and adjacent tissue.